A systematic review of the main mechanisms of heart failure disease management interventions. (23rd February 2016) - Clark, Alexander M; Wiens, Kelly S; Banner, Davina; Kryworuchko, Jennifer; Thirsk, Lorraine; McLean, Lianne; Currie, Kay
Abstract : Objective: To identify the main mechanisms of heart failure (HF) disease management programmes based in hospitals, homes or the community. Methods: Systematic review of qualitative and quantitative studies using realist synthesis. The search strategy incorporated general and specific terms relevant to the research question: HF, self-care and programmes/interventions for HF patients. To be included, papers had to be published in English after 1995 (due to changes in HF care over recent years) to May 2014 and contain specific data related to mechanisms of effect of HF programmes. 10 databases were searched; grey literature was located via Proquest Dissertations and Theses, Google and publications from organisations focused on HF or self-care. Results: 33 studies (n=3355 participants, mean age: 65 years, 35% women) were identified (18 randomised controlled trials, three mixed methods studies, six pre-test post-test studies and six qualitative studies). The main mechanisms identified in the studies were associated with increased patient understanding of HF and its links to self-care, greater involvement of other people in this self-care, increased psychosocial well-being and support from health professionals to use technology. Conclusion: Future HF disease management programmes should seek to harness the main mechanisms through which programmes actually work to improve HF self-care and outcomes, rather than simply replicating components from other programmes. The most promising mechanisms to harness are associated with increased patient understanding and self-efficacy, involvement of other caregivers and health professionals and improving psychosocial well-being and technology use.